Palomar - Calvino, Italo; Bernárdez, Aurora; Calvino, Italo (Madrid : Siruela, 2012)
Relates the inner dialogs, reflections, and musings of Mr. Palomar.
Online resource; title from ePub title page (Digitalia, viewed March 12, 2016)
Keywords: Philosophy -- Fiction; Allegories; Electronic books